Pengaruh Model Pembelajaran PBL dengan Pendekatan Diferensiasai Materi Harmoni dalam Ekosistem terhadap Hasil Belajar Siswa SD Kelas 5 - Mega Puspitasari (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research aims to analyze the influence of the problem based learning model with a differentiation approach to the topic of harmony in the ecosystem of grade 5 elementary school students. The population in this study was class V students at Wadungasri Elementary School, Waru District, Sidoarjo Regency, totaling 77 students and a sample of 29 students was taken. Data collection techniques using questionnaires. Data processing techniques with validity testing using expert judgment techniques. Reliability test uses Alpha Cronbach. The swimmer analysis test is the normality test and linearity test. The data analysis technique used is a simple regression test. Research results: the guided inquiry learning model had an effect on students' critical thinking skills by 3.7%. The research results show that the problem based learning model with a differentiation approach to the topic Harmony in ecosystems is significantly effective in increasing students' understanding of ecosystems.